2011
DOI: 10.1021/ja205226d
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM Analysis Suggests That Alkaline Phosphatase (AP) and Nucleotide Pyrophosphatase/Phosphodiesterase Slightly Tighten the Transition State for Phosphate Diester Hydrolysis Relative to Solution: Implication for Catalytic Promiscuity in the AP Superfamily

Abstract: Several members of the Alkaline Phosphatase (AP) superfamily exhibit a high level of catalytic proficiency and promiscuity in structurally similar active sites. A thorough characterization of the nature of transition state for different substrates in these enzymes is crucial for understanding the molecular mechanisms that govern those remarkable catalytic properties. In this work, we study the hydrolysis of a phosphate diester, MpNPP−, in solution, two experimentally well-characterized variants of AP (R166S AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
116
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(133 citation statements)
references
References 97 publications
(271 reference statements)
16
116
1
Order By: Relevance
“…That is, it was shown that the TS character is again dependent on the pK a of the leaving group, with a compact associative A N D N TS at high pK a that becomes progressively more expansive as the leaving group becomes more acidic (despite reproducing the LFER with chemical accuracy). Interestingly, this study covered a much smaller pK a range than that of the monoester dianions ; however, the overall correlation between leaving group pK a and mechanism appears to be similar, and qualitatively similar TSs have recently been obtained using QM/MM studies (Hou & Cui, 2012).…”
Section: The Mechanism(s) Of Phosphate Diester Hydrolysissupporting
confidence: 63%
See 4 more Smart Citations
“…That is, it was shown that the TS character is again dependent on the pK a of the leaving group, with a compact associative A N D N TS at high pK a that becomes progressively more expansive as the leaving group becomes more acidic (despite reproducing the LFER with chemical accuracy). Interestingly, this study covered a much smaller pK a range than that of the monoester dianions ; however, the overall correlation between leaving group pK a and mechanism appears to be similar, and qualitatively similar TSs have recently been obtained using QM/MM studies (Hou & Cui, 2012).…”
Section: The Mechanism(s) Of Phosphate Diester Hydrolysissupporting
confidence: 63%
“…There have been a number of recent computational studies that have attempted to explore the issue of the comparative size of the TS for the solution and AP/NPP catalyzed hydrolysis of phosphate diesters (Hou & Cui, 2012 ;López-Canut et al 2010, 2011, which have obtained sharply contrasting results. López-Canut and co-workers (López-Canut et al 2010, 2011 have proposed that in both NPP and AP, phosphodiester hydrolysis proceeds through far more dissociative TS in the enzyme active site than in solution.…”
Section: The Electrostatic Basis For Catalytic Promiscuity In the Alkmentioning
confidence: 99%
See 3 more Smart Citations